Book Review - Gan, Ching Chuan (Journal of Malaysian and Comparative Law, 2019)
Administrative Law is growing at a rapid pace since the 1960s throughout the common law world. Since the appearance of the first edition of this book, so much development and change have taken place in this branch of law both at home and abroad. In order to keep pace with this rapid progress, the second edition of this book has been keenly awaited.